Perception Analysis of the Use of Digital Wallets in East Kalimantan Province Students - Dewi Atriani; Eliyah A. M. Sampetoding; Avi Sunani; Sabrina W. J. Husain; Arini A. Purba (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to analyse the perceived convenience and perceived risk in the use of e-wallet among students in the province of East Kalimantan. This research is based on primary data in the form of a online survey of 113 East Kalimantan’s student who using e-wallet. The results of this study were found that more than half of the respondents agreed on the aspect of perceived convenience and the aspect of perceived risk. Respondents felt that the e-wallet was easy to use and felt safe using it. The results of this study are expected to open up further and useful research for the benefit of academics as well as technological and economic developments.